The Influence of Occupational Safety and Health and the Work Environment on Employee Performance at PT. PLN PDKB KSKT Unit - Edy Mahfuz; Junaidi Junaidi; Muhammad Haris Syafitri; Abdul Kadir; Orbawati Orbawati (Management Dynamics: International Journal of Management and Digital Sciences, 2025)
Things that is done by the company can be in the form of occupational safety and health training aimed at improving knowledge , skills , attitudes that are physically designed according to the work needs of each employees . In addition , protective equipment is also called Personal Protective Equipment (PPE) which is equipment used by all employees without exception to protect themselves from potential workplace accidents . There are several elements that can support occupational safety , namely elements of occupational safety and security such as awareness in maintaining occupational safety and health , being thorough , implementing work procedures by pay attention to occupational safety and health . Good occupational safety is an important dimensions of employee protection . This protection aiming for employees to safely carry out their daily work so that they can improve industrial productivity performance . PT. PLN (Persero) Unit PDKB KSKT is a State- Owned Enterprise (BUMN) whose purpose is in the field of distributing electrical energy PT. PLN (Persero) serves the electricity needs of the community such as submitting applications for electricity installations , submission applications for increasing voltage or adding power , checking PLN electricity bills , paying electricity to complan